(untitled) (Damascus University Journal of arts and humanities sciences, 2022)
The research aims to plan for the optimal investment of water resources in the basin. The research problem was manifested by not evaluating the rate of runoff (The Flow) Qm3/s. Water wastage and lack of dams. According to the water dividing, the basin was divided to (13) hydrological basins. These basins have (12) main basins and a sub basin ) the basin of Bait Al-Qasyr Dam). It was also divided according to the rate of precipitation at the level of metrological stations, the affective precipitation rate, the runoff factor, the rate of the surface runoff volume and the rate of the renewable groundwater volume. The affective precipitation reached to (43.7) mm3, the rate of the surface runoff volume (10.5) mm3, the rate of the renewable groundwater volume in the basin (33.2) mm3 and the amount of the water wastage (10.4) mm3. A mathematical model was established for the rate of the surface runoff and the rate of the volume of the renewable groundwater. The water waste in the sea is reduced by building dams on the waterway in the basin